The current progress and critical analysis of three-dimensional scanning and three-dimensional printing applications in breast surgery. Issue 3 (8th April 2021) - Alshehri, S A; Singh, S K; Mosahebi, A; Kalaskar, D M
Abstract: Background: Several attempts have been made to develop a tool capable of evaluating breast shape and volume to aid surgical planning and outcome assessment. More recently, newer technologies such as three-dimensional (3D) scanning and 3D printing have been applied in breast assessment. The aim of this study was to review the literature to assess the applicability of 3D scanning and 3D printing in breast surgery. Methods: A literature search was carried on PubMed, Google Scholar and OVID from January 2000 to December 2019 using the keywords '3D', 'Three-dimensional', 'Three/four dimensions' and 'Breast'. Results: A total of 6564 articles were identified initially; the abstracts of 1846 articles were scanned, and 81 articles met the inclusion criteria and were included in this review. Articles were reviewed and classified according to their aims, study subjects, the software and hardware used, main outcomes and major limitations. Conclusions: These technologies are fast and easy to use, however, high costs, long processing times and the need for training might limit their application. To incorporate these technologies into standard healthcare, their efficacy and effectiveness must be demonstrated through multiple and rigorous clinical trials. Abstract : 3D scanning and 3D printing have been applied and investigated in breast surgery with promising potential. Although these technologies are fast and easy to use, increased costs, long processing time and the need for training might limit their application. Needs further study